Manifestations of the mythic double self in the poetic voices of Fernando Pessoa, Antonio Machado and Juan Ramón Jiménez - Lorenzo García, Esther (Amaltea. Revista de Mitocrítica, 2011)
In poetry, the motif of the mythic double self applies to duplicities perceived by the poetic self during the process of exploring both the world and the poet’s own conscience. In the writers here examined (Antonio Machado, Fernando Pessoa and Juan Ramón Jiménez) this motif can be seen through three basic, non-excluding patterns: as the longing for fullness, as a bridge to others, and as metaphor of a divided character. In all these cases, one can find rewritings which draw on literary tradition, from the Platonic dialogues – the dual origin of mankind, the poet as ‘possessed’, etc. – to the Doppelgänger.